SURPLUS BERAS YANG DAPAT DIJUAL DAN FAKTOR-FAKTOR PENENTUNYA DI DAERAH SENTRA PRODUKSI SUMATERA SELATAN - Mulyana, Andy; Antoni, Mirza; Riswani, . (Indonesian Journal of Socio Economics)
Farmers perform double roles at the same time in treating rice commodity, that are as producers and as consumers. This research tried to find out the average amount of rice marketable surplus at the hand of farmersâ households and to analyze which variables significantly influence the surplus.Â  The results of the research conducted in four rice production centres od South Sumatra reveal that the average rice consumption of famersâ households were 98,42 kg per person or 402.75 kg per household with 4 members, while their rice production were 5842,75 kg per household.Â  Farmers in all rice production centers have actually carried out marketable surplus on their rice production as their consumed a portion as needed and sold the majority amounts to the market.Â  There were variations of rice consumed between rice production centers.Â  Rice marketable surplus in all production centers (OKU Timur, OKI, Musi Rawas and Banyuasin) were significantly influenced by rice production.Â  In three production centers, the rice production also was influenced significantly by the number of household members and off-farm income, while in two production centers, it was also determined by rice price and age composition of farmer family members. Â The other variables affected rice marketable surplus exclusively in each area. Â Â Â Â Â Â Â